AB0893 Disease related knowledge in gout patients and the relationship with adherence to urate-lowering therapy in east china. (15th June 2017) - Yin, R; Fu, T; Zhang, Q; Zhang, L; Li, L; Gu, Z
Abstract : Background: Gout is a chronic rheumatic disease caused by deposition of monosodium urate crystals in and around the joint, with a reported prevalence of 1.1% in mainland China and 6.24% in Taiwan, making it the most common form of inflammatory arthritis. With the disease progression, gout can cause permanent joint destruction, bone erosion, and organ damage. Urate-lowering therapy (ULT) is necessary to lower and maintain serum urate (sUA) levels at a therapeutic target of <360 μmol/L as this is associated with fewer gout flares, reduction of tophus size, and depletion of urate crystal stores in synovial tissues, making gout the only chronic arthritis that can be "cured". Disease related knowledge of gout patients should be assessed before attempting to improve health education.To date, except one study from south China, all other published papers about gout knowledge and medication adherence are from other countries. To our knowledge, there is no survey from east China. Objectives: The current study aimed to investigate knowledge related to gout and it's risk factors, and the relationship with adherence to urate-lowering therapy in patients with gout in east China. Methods: A cross-sectional study of 229 gout patients recruited from the Affiliated Hospital of Nantong University between August 2015 and November 2016 was conducted with two questionnaire, Gout Knowledge Questionnaire (GKQ) and Compliance Questionnaire on Rheumatology (CQR). Chi-square analysis, t-test, rank sum test, as well as logistic regression analysis were used to analyze data. Results: 21.5% (49/228) of gout patients in east China had knowledge of gout, and 9.1% (13/143) adhered to ULT. Age, employment, income, alcohol use, family history, acute flares in preceding 1 year, and colchicine use were associated with awareness of gout-related knowledge, and age, income, alcohol use, and colchicine use were the predictors. Among patients with ULT, patients adherent to ULT tended to have gout-related knowledge, compared with non-adherent patients. Awareness of the cause of gout attack, flare prevention induced by ULT and comorbidity were correlated with medication adherence, and the cause of gout attack as well as flare prevention induced by ULT were predictors of adherence to ULT in gout patients in east China. Conclusions: In this study, 78.5% of patients in east China didn't have gout-related knowledge. Patients' knowledge on gout is a significant independent determinant of adherence to ULT. Acknowledgements: This study was supported by grants from the Cultivative Distinguished Young Scholars Project of Nantong University (2nd);the 2015 Graduate Innovation Project of Nantong University (YKC15075); and College graduate research and innovation of Jiangsu Province (KYZZ15–0353). Disclosure of Interest: None declared